Naming rights deals: fans' perceptions and expected behaviours - Patah, Rodrigo Chehab (2021)
The COVID-19 pandemic caused an unprecedented disruption to sports all around the world, since matches had to be played behind closed doors, broadcast rights were renegotiated and sponsor brands were pushed to rethink their investments. The objective of this study is to find out if naming rights deals could be a conceivable alternative for football clubs and sponsor brands in the context of the pandemic, by assessing the fans perceptions toward this topic and by understanding the factors that influence fans’ reactions to this kind of negotiation. Previous studies about the topic had showed mixed results: in some cases, a part of the fans presented a strong criticism to naming rights commercialization and to the sponsor brand, whereas in other situations some types of contextual factors seemed to reduce resistance. In order to collect subsidies about the subject, a survey and an experiment were conducted with Brazilian fans. This study decided to focus in Brazil with the aim of expanding the literature related to the topic, as it had been previously concentrated in developed markets such as USA and Germany.